Novel Wide-Band Dielectric Imaging System Guided Lead Deployment for His Bundle Pacing: A Feasibility Study - Hua, Wei; Liu, Xi; Gu, Min; Niu, Hong-xia; Chen, Xuhua; Tang, Min; Zhang, Shu (Frontiers in Cardiovascular Medicine, 2021)
Introduction: His bundle pacing (HBP) is the most physiological pacing modality, but with higher fluoroscopic exposure due to difficulties in locating the His bundle. Electroanatomical mapping (EAM) system can be an efficient tool to achieve HBP implantation with zero fluoroscopic visualization. Methods: Twenty patients who had indications for pacemaker implantation were prospectively enrolled and underwent HBP implantation with either the conventional fluoroscopy approach (the standard group) or guided by a novel KODEX-EPD mapping system (the EAM guided group). The success rate, procedural details, pacing parameters and procedural related complications were compared between two groups. Results: Twenty consecutive patients were randomized with 10 patients in each group. HBP was successfully achieved in 9 patients in the standard group and in 9 in the EAM guided group. The procedural time was similar between the EAM guided group versus the standard group (85.67 ± 15.72 min vs. 80.22 ± 16.12 min, p = 0.48). Compared with the standard group, the total fluoroscopic time (1.29 ± 0.28 min vs. 10.99 ± 3.51 min, p < 0.01) and the His lead fluoroscopic time (0.68 ± 0.24 min vs. 7.77 ± 2.81 min, p < 0.01) in the EAM guided group were significantly shorter, the total fluoroscopic dose (2.78 ± 0.57 mGy vs. 22.64 ± 7.46 mGy, p < 0.01) and the His lead fluoroscopic dose (1.51 ± 0.50 mGy vs. 16.07 ± 6.01 mGy, p < 0.01) were significantly lower. No significant differences were observed in paced QRS duration and pacing parameters between two groups. During 3-month follow-up, one patient had an increased level >1V/1.0ms in capture threshold in the standard group, while no other complications were recorded. Conclusions: The KODEX-EPD system could facilitate HBP implantation with significant reduced fluoroscopic time and dose without compromising the procedural time.